Pengembangan Modul Menulis Kalimat Efektif untuk Siswa Kelas IV SD - Dita Dwi Anggraini; Muh. Arafik; Titis Angga Rini; Dita Dwi Anggraini; Muh. Arafik (Universitas Negeri Malang, 2023)
Abstract: The problem that researchers found at SDN Bumiayu 03 is that students still have difficulty using effective sentences when learning Indonesian. This difficulty is due to the incomplete coverage of the material in learning Indonesian, especially the effective sentence material presented in the student book. The existing books are still lacking in variety and lack of examples and practice questions. Teachers in learning only use thematic books without any additional teaching materials that support Indonesian language learning, especially effective sentence material. The aim of the research and development is to produce an effective sentence writing module for fourth grade students at SDN Bumiayu 03 which is valid according to material experts, teaching materials experts and practice for students and teachers as users.The ADDIE model is used in this research and development, which includes analysis, planning, development, implementation, and evaluation. According to the findings of this study, the material expert validation test received 93.1 percent (very valid), the teaching material expert validation test received 97.9 percent (very valid), the student response questionnaire received 95.3 percent (very practical), and the user practicality test received 97.5 percent. (very practical). The conclusions from the development research results above show that the product of the Effective Sentence Writing module for Grade IV Students at SDN Bumiayu 03 is appropriate for use in learning activities. Abstrak: Masalah yang peneliti temukan di SDN Bumiayu 03 adalah siswa masih kesulitan dalam menggunakan kalimat efektif ketika pembelajaran bahasa Indonesia. Kesulitan ini dikarenakan cakupan materi dalam pembelajaran bahasa Indonesia khususnya materi kalimat efektif yang disajikan dalam buku siswa kurang lengkap. Buku yang ada masih kurang bervariasi dan kurang banyak contoh dan latihan soal. Guru dalam pembelajaran hanya menggunakan buku tematik saja tanpa adanya tambahan bahan ajar lain yang mendukung pembelajaran bahasa Indonesia khususnya materi kalimat efektif. Tujuan dari penelitian dan pengembangan untuk menghasilkan modul menulis kalimat efektif bagi siswa kelas IV SDN Bumiayu 03 valid menurut ahli materi, ahli bahan ajar dan praktis untuk siswa serta guru sebagai pengguna. Model ADDIE digunakan dalam penelitian dan pengembanga ini, yang meliputi analisis, perencanaan, pengembangan, implementasi, dan evaluasi. Berdasarkan temuan penelitian ini, uji validasi ahli materi diperoleh 93,1 persen (sangat valid), penilaian uji validasi ahli bahan ajar diperoleh 97,9 persen (sangat valid), dan hasil angket respon siswa diperoleh 95,3 persen (sangat praktis), serta uji kepraktisan pengguna diperoleh 97,5 persen (sangat praktis). Kesimpulan hasil penelitian pengembangan di atas, menunjukkan bahwa produk modul Menulis Kalimat Efektif Untuk Siswa Kelas IV SDN Bumiayu 03 layak digunakan dalam kegiatan pembelajaran.